Altered Kinematics of Facial Emotion Expression and Emotion Recognition Deficits Are Unrelated in Parkinson’s Disease - Bologna, Matteo; Berardelli, Isabella; Paparella, Giulia; Marsili, Luca; Ricciardi, Lucia; Fabbrini, Giovanni; Berardelli, Alfredo (Frontiers in Neurology, 2016)
Background: Altered emotional processing, including reduced emotion facial expression and defective emotion recognition, has been reported in patients with Parkinson’s disease (PD). However, few studies have objectively investigated facial expression abnormalities in PD using neurophysiological techniques. It is not known whether altered facial expression and recognition in PD are related. Objective: To investigate possible deficits in facial emotion expression and emotion recognition and their relationship, if any, in patients with PD. Methods: Eighteen patients with PD and 16 healthy controls were enrolled in the study. Facial expressions of emotion were recorded using a 3D optoelectronic system and analysed using the facial action coding system. Possible deficits in emotion recognition were assessed using the Ekman test. Participants were assessed in one experimental session. Possible relationship between the kinematic variables of facial emotion expression, the Ekman test scores and clinical and demographic data in patients were evaluated using the Spearman’s test and multiple regression analysis. Results: The facial expression of all six basic emotions had slower velocity and lower amplitude in patients in comparison to healthy controls (all Ps<0.05). Patients also yielded worse Ekman global score and disgust, sadness and fear sub-scores than healthy controls (all Ps<0.001). Altered facial expression kinematics and emotion recognition deficits were unrelated in patients (all Ps>0.05). Finally, no relationship emerged between kinematic variables of facial emotion expression, the Ekman test scores and clinical and demographic data in patients (all Ps>0.05). Conclusion: The present results provide further evidence of altered emotional processing in PD. The lack of any correlation between altered facial emotion expression kinematics and emotion recognition deficits in patients suggests that these abnormalities are mediated by separate pathophysiological mechanisms.